Sikap dan Kebiasaan Belajar Mahasiswa - Wilda, Ayu Gusni; Syukur, Yarmis; Nurfahanah, Nurfahanah (Konselor, 2014)
Abstract: Attitude and habit of good learning can support activity of lecturing. However, still lack of awareness student about the important of doing duties which given by lecturer. The purpose of this research is for description about habit and attitude of learning by student. This research factioned quantitative research of descriptive type. The population of this research is 211 responder and the sample is 53 responder. The instrument of this Research using a quetioner. The Result of research showing that attitude of learning student categorized is good with percentage 61.4%, while habit learn student categorized is good with percentage 67.0%. Conclusion: attitude of learning student categorized is good and attitude of learning student categorized is good. Suggestion: student must be apply good habit and attitude in learning process and on time to come in lecturing, doing duty, well-read book related to lecturing, repeat studying the lessons with friend and eliminate excitement bothering lecturing.